2010
DOI: 10.1088/0004-637x/720/1/494
|View full text |Cite
|
Sign up to set email alerts
|

Solar Rotation Rate During the Cycle 24 Minimum in Activity

Abstract: The minimum of solar cycle 24 is significantly different from most other minima in terms of its duration as well as its abnormally low levels of activity. Using available helioseismic data that cover epochs from the minimum of cycle 23 to now, we study the differences in the nature of the solar rotation between the minima of cycles 23 and 24. We find that there are significant differences between the rotation rates during the two minima. There are differences in the zonal-flow pattern too. We find that the ban… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
(60 reference statements)
3
21
1
Order By: Relevance
“…It is interesting to note that the average rotation rate (∼438 nHz) we have measured in CHs ( Figure 13) is similar to that of the average rotation rate of the solar plasma inferred by helioseismology (Antia & Basu 2010; rotation rate of the solar interior averaged over one solar cycle is kindly provided by Prof. Antia) at a depth of ∼0.62(±0.10) R . Hence, during the first CHs' appearance, it is reasonable to suggest that the depth of anchoring of CH might be around 0.62(±0.10) R .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is interesting to note that the average rotation rate (∼438 nHz) we have measured in CHs ( Figure 13) is similar to that of the average rotation rate of the solar plasma inferred by helioseismology (Antia & Basu 2010; rotation rate of the solar interior averaged over one solar cycle is kindly provided by Prof. Antia) at a depth of ∼0.62(±0.10) R . Hence, during the first CHs' appearance, it is reasonable to suggest that the depth of anchoring of CH might be around 0.62(±0.10) R .…”
Section: Discussionsupporting
confidence: 73%
“…The rotation rate of the interior and the surface are coupled with the rotation rate of the solar atmosphere, especially the corona. Although there is a general consensus regarding the interior rotation as inferred from helioseismology (Dalsgaard & Schou 1988;Thompson et al 1996Thompson et al , 2003 and references therein; Antia et al 1998;Howe 2009;Antia & Basu 2010), surface rotation rates as derived from sunspots (Newton & Nunn 1951;Howard et al 1984;Balthasar et al 1986;Shivaraman et al 1993;Javaraiah 2003), Doppler velocity (Howard & Harvey 1970;Howard & La Bonte 1980;Ulrich et al 1988;Snodgrass & Ulrich 1990), and magnetic activity features (Wilcox & Howard 1970;Snodgrass 1983;Komm et al 1993), there is no such consensus (see also Li et al 2012) on the magnitude and form of the rotation law for features in the corona.…”
Section: Introductionmentioning
confidence: 99%
“…The rotation rate of sunspots varies with area and age (Ward 1966;Howard et al 1984;Zappalá & Zuccarello 1991), which has been suggested to be due to the different anchor depths of different types of sunspots (Nesme-Ribes et al 1993;Rhodes et al 1990). Moreover, the differential rotation of all tracers of rotation is also affected by large-and small-scale flows, such as torsional oscillations (Covas et al 2001;Howe et al 2009;Antia & Basu 2010), meridional flows (Javaraiah & Ulrich 2006;Javaraiah 2010;Nandy et al 2011), supergranules (Beck & Schou 2000), etc. Therefore, shortening the fit period reveals the detailed variation of rotation at short time scales, yielding more accurate momentary rotation rates, stronger non-axisymmetries and and a higher accuracy when finding ALs.…”
Section: Discussionmentioning
confidence: 99%
“…With the significant differences between the onset of solar cycles 23 and 24 it was also discovered that differences are present in the torsional oscillation pattern (Howe et al 2009(Howe et al , 2011Antia & Basu 2010). In low latitudes the overall rate of propagation toward the equator is reduced, consistent with the later onset of cycle 24.…”
Section: Introductionmentioning
confidence: 87%